Associations between kidney injury markers and COVID-19 severity: A retrospective study from a tertiary hospital - AlBahrani, Salma; Al-Maqati, Thekra N; Al-Jamea, Lamiaa Hamad; Al Khalaf , Faisal Salem; Maawadh , Rawan M; Nazzal , Wael; Suliman , Rania Saad; Allahow, Abrar Ahmed; Al Asmari , Rashid Ali; Alghamdi , Mansour Yeanallah; Alshehri , Sultan Ali; AlQarni , Abdullah Ali; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: COVID-19 pandemic has been linked with many organ complications, among them being acute kidney injury (AKI), which is related to worse clinical outcomes. Understanding the relationship between renal biomarkers and disease severity is important in providing early detection and better management of high-risk patients. The current study explores the correlation between biomarkers of kidney injury and COVID-19 severity in hospitalized patients at a Saudi Arabian tertiary care hospital. Methods: A retrospective, single-centre, study was conducted on 450 adult patients who were hospitalized with laboratory-confirmed COVID-19 between March 2020 and December 2021. Demographics, comorbidities, clinical outcomes, and renal biomarkers including serum creatinine, blood urea nitrogen (BUN), sodium, potassium, chloride, and CO₂ were assessed. Statistical testing and multinomial logistic regression were used to assess the association of biomarker levels with disease severity (mild, severe, critical). Results: Elevated BUN was strongly associated with critical group (46.7%) compared to severe (23.6%) and mild (22.8%) cases (p < 0.001). Abnormal potassium, chloride, and CO₂ levels were also strongly associated with severity. The creatinine and sodium levels, however, were not significantly associated. Logistic regression validated BUN as an independent predictor of severity (OR for critical = 1.125, p < 0.001), whereas potassium and chloride demonstrated reverse relationships with severity levels. There was weak reverse correlation of creatinine. Conclusion: BUN, potassium, and chloride may serve as useful indicators of COVID-19 severity and could be useful biomarkers for the early risk stratification. Compliance with these parameters may facilitate early intervention and improve clinical outcomes in COVID-19 patients with AKI.